2007
DOI: 10.1525/sp.2007.54.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Group Position, Collective Threat, and American Anti-Semitism

Abstract: This article provides a theoretical account of anti-Jewish prejudice and empirically tests this model using data from a recent national survey of adults in the United States. Whereas much prior research emphasizes the religious and cultural foundations of anti-Semitism, the present research provides an alternative framework that builds on Herbert Blumer's (1958) theory of prejudice as a sense of group position. Two related yet distinct lines of research have evolved from Blumer's seminal work, one emphasizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Our cultural analysis of the Gypsy Threat Narrative is, of course, preliminary, but the findings remained robust while accounting for measures of other explanations of threat and racial prejudice (Blumer 1958;King and Weiner 2007;Quillan 1995). In unreported exploratory models, we included country-level measures of inequality, ethnic heterogeneity, size of Roma population, migration, and UN human development measures, but none produced statistically significant results.…”
Section: Discussionmentioning
confidence: 70%
“…Our cultural analysis of the Gypsy Threat Narrative is, of course, preliminary, but the findings remained robust while accounting for measures of other explanations of threat and racial prejudice (Blumer 1958;King and Weiner 2007;Quillan 1995). In unreported exploratory models, we included country-level measures of inequality, ethnic heterogeneity, size of Roma population, migration, and UN human development measures, but none produced statistically significant results.…”
Section: Discussionmentioning
confidence: 70%
“…In the list of stereotypes used by ADL in its Global 100 Anti-Semitism Index, 6 out of 11 items are about Jews having excessive power: in business, finances, global affairs, government, global media, and being responsible for most of the wars (ADL, 2015). A strong belief that Jews have too much power and influence, and they seek dominance over the world, especially through controlling financial institutions, was found in several American and European studies (Cohen, 2018;King & Weiner, 2007;Kofta & Sedek, 2005;Konig et al, 2017;Smith, 1993;Weil, 1990). Moreover, surveys conducted in Russia have demonstrated that the power stereotypes of Jews are widespread in this country (Gibson & Duch, 1992;Gibson & Howard, 2007;Korey, 1972;Leach et al, 2008).…”
Section: Powermentioning
confidence: 99%
“…Stereotypes related to power are the most salient and widespread among all Jewish stereotypes (King & Weiner, 2007). The classic study by Katz and Braly (1935), as well as its latter replications (Madon et al, 2001), have demonstrated that Jews are often perceived as mercenary, grasping, materialistic, business-oriented, practical, and wealthy.…”
Section: Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, when White Americans are asked whether it is acceptable to hold prejudices toward Black Americans, their answer tends to be a resounding “no.” Even when surveyed privately and anonymously, respondents indicate that it is considered more acceptable to hold prejudices toward doctors, spelling bee champions, and even White Americans than toward Black Americans (Crandall, Eshleman, & O’Brien, 2002). Similarly, despite the ongoing prevalence of anti‐Semitism (see King & Wiener, 2007) and prejudice toward individuals with physical disabilities (for a review, see Stone & Colella, 1996), nearly identical consensus is found for norms of prejudice unacceptability toward Jews and individuals with physical disabilities (Crandall et al, 2002).…”
mentioning
confidence: 99%